Primary malignancy in giant cell tumor: a case report - Bispo Júnior, Rosalvo Zósimo; Camargo, Olavo Pires de; Ida, Cristiane Marie; Baptista, André Mathias; Ribeiro, Marcelo Barbosa; Bruno, José Marcello; Oliveira, Cláudia Regina Gomes Cardim Mendes de (São Paulo Medical Journal, 2009)
CONTEXT: Primary malignancy in giant cell tumor (PMGCT) is rare. It is defined as a high-grade sarcoma originating in a giant cell tumor (GCT) and seems to behave less aggressively than its secondary counterpart does. CASE REPORT: This report presents the case of a 39-year-old female with pain in her left shoulder for one month. Radiography showed a pathological fracture of the proximal humerus associated with an osteolytic lesion. Histopathological analysis showed typical areas of GCT juxtaposed with a sarcomatous component. CONCLUSIONS: PMGCT seems to behave less aggressively than secondary malignancy in GCT, and it may simulate its more common benign counterpart clinically and radiographically. However, it requires a more aggressive type of treatment.